Looking for a Few Good Metrics: Automatic Summarization Evaluation - How Many Samples Are Enough? - Lin, Chin-Yew (NTCIR 2004 (NTCIR-4), 2004)
ROUGE stands for Recall-Oriented Understudy for Gisting Evaluation. It includes measures to automatically determine the quality of a summary by comparing it to other (ideal) summaries created by humans. The measures count the number of overlapping units such as n-gram, word sequences, and word pairs between the computer-generated summary to be evaluated and the ideal summaries created by humans. This paper discusses the validity of the evaluation method used in the Document Under-standing Conference (DUC) and evaluates five different ROUGE metrics: ROUGE-N, ROUGE-L, ROUGE-W, ROUGE-S, and ROUGE-SU included in the ROUGE summarization evaluation package using data provided by DUC. A comprehensive study of the effects of using single or multiple references and various sample sizes on the stability of the results is also presented.